The story of the Ulul Azmi Prophets in the Qur'an and its relationship with Emotional Intelligence - Octaviana, Okky (UIN Sunan Gunung Djati Bandung, 2025)
The Ulul Azmi prophets in the Qur’an—Nuh, Ibrahim, Musa, Isa, and Muhammad SAW—faced deep psychological conflicts amid severe trials from their communities. This study explores their inner struggles and the moral and psychological lessons (ibrah) relevant to developing emotional intelligence today. Using qualitative thematic interpretation and interdisciplinary analysis combining tafsir and psychology, it reveals unique emotional challenges for each prophet: Nuh’s frustration from rejection, Ibrahim’s dilemma over sacrificing his son, Musa’s trauma and guilt, Isa’s social pressures, and Muhammad’s burden of leadership and rejection. Their responses demonstrated core emotional intelligence traits like regulation, patience, empathy, and resilience. The prophetic narratives thus provide valuable lessons for emotional and spiritual resilience in modern life. The Ulul Azmi prophets in the Qur’an—Nuh, Ibrahim, Musa, Isa, and Muhammad SAW—faced deep psychological conflicts amid severe trials from their communities. This study explores their inner struggles and the moral and psychological lessons (ibrah) relevant to developing emotional intelligence today. Using qualitative thematic interpretation and interdisciplinary analysis combining tafsir and psychology, it reveals unique emotional challenges for each prophet: Nuh’s frustration from rejection, Ibrahim’s dilemma over sacrificing his son, Musa’s trauma and guilt, Isa’s social pressures, and Muhammad’s burden of leadership and rejection. Their responses demonstrated core emotional intelligence traits like regulation, patience, empathy, and resilience. The prophetic narratives thus provide valuable lessons for emotional and spiritual resilience in modern life.